LAMA FERMENTASI TERHADAP MUTU COCOGHURT MENGGUNAKAN Enterecoccus faecalis UP-11 YANG DIISIOLASI DARI TEMPOYAK - Muhammad Nur Imam; Usman Pato; Faizah Hamzah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Coconut milk is usually used as condiment for production various Indonesia traditional cuisine  coconut milk can be also used as raw material for making cocoghurt because of it is high nutrional value. The purpose of this research was to determine the effect of fermentation time on the  quality of cocoghurt . The research used a Completely Randommized Design with five treatments, T1 (duration of fermentasi in three hours), T2 (duration of fermentation in six hours), T3 (duration of fermentation in nine hours), T4 (duration of fermentation in twelve hours) and T5 (duration of fermentation in fifteen hours) with three replication. The data was analyzed using ANNOVA, if any influence continued with DNMRT test at 5%. Results show that fermentation time significantly (P<0,05) affected the pH, total lactid acid, fat content, organoleptic test of colour, texture, sweetness, and hedonik. But did not significantly influence (P>0.05)  total solids, ash content,  protein content, total lactid acid bacteria, test organoleptik of flavor, and  taste. It was concluded that the best quality of cocoghurt. Was obtained in the fermentation time of six hours (T2), that meets the Indonesian yoghurt standard (SNI 102981: 2009) as  total lactid acid, fat content, total solids, ash content,  and protein content.   Keywords: Duration of fermentation, Enterecocus faecalisUP-11, Tempoyak, Cocoghurt.